2017
DOI: 10.1007/s00204-017-2013-y
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans

Abstract: Pyrrolizidine alkaloids (PAs) are among the most potent phytotoxins widely distributed in plant species around the world. PA is one of the major causes responsible for the development of hepatic sinusoidal obstruction syndrome (HSOS) and exerts hepatotoxicity via metabolic activation to form the reactive metabolites, which bind with cellular proteins to generate pyrrole-protein adducts, leading to hepatotoxicity. PA N-oxides coexist with their corresponding PAs in plants with varied quantities, sometimes even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 38 publications
6
90
0
1
Order By: Relevance
“…Serum pyrrole protein adducts (PPAs) are of clinical value in suspected PA–HSOS patients with an uncertain history of ingesting PA‐containing . Both PAs and PA N ‐oxides were identified in 18 samples of Gynura segetum ingested by patients with liver damage . A prospective study by Gao et al .…”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Serum pyrrole protein adducts (PPAs) are of clinical value in suspected PA–HSOS patients with an uncertain history of ingesting PA‐containing . Both PAs and PA N ‐oxides were identified in 18 samples of Gynura segetum ingested by patients with liver damage . A prospective study by Gao et al .…”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%
“…2,3 Both PAs and PA N-oxides were identified in 18 samples of Gynura segetum ingested by patients with liver damage. 60 A prospective study by Gao et al found that a serum PPA assay correctly distinguished 23 of 40 patients with liver injury and a history of PA-containing medicines from the 17 with liver injury caused by drugs that did not contain PA. 38 The findings indicated that serum PPAs had a diagnostic sensitivity of 100.0%, a specificity of 94.1%, a positive predictive value of 95.8%, and a negative predictive value of 100.0%. Blood PPAs assayed by ultra-high-performance liquid chromatography-triple quadrupole-mass spectrometry can serve as a specific biomarker of PA-induced liver injury.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…The main reason is that it is easy to use Tusanqi is that it is similar to the precious traditional Chinese medicine Panax notoginseng, which has functions including the promotion of blood circulation, the removal of blood stasis and the relief of swelling and pain. When PAs contained in herbal medicines are ingested into the body, metabolites generated under the catalysis of the hepatic cytochrome P450 enzyme combine with proteins to form pyrrole protein adducts, which damage sinusoidal endothelial cells, cause the exfoliated endothelial cells to aggregate in the central lobular area, and form cell emboli, resulting in intrahepatic congestion, liver function damage and portal hypertension [21][22] . Binding to GSH is one of the most important detoxification reactions of PA.…”
Section: Discussionmentioning
confidence: 99%
“…A broad range of plant species have been identified that produce toxic 1,2‐dehydro‐pyrrolizidine alkaloids (PAs) as secondary metabolites . These PAs are potent phytotoxins exerting hepatotoxicity and carcinogenicity . In recent years, the appearance of Senecio spp.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These PAs are potent phytotoxins exerting hepatotoxicity and carcinogenicity. 3,4 In recent years, the appearance of Senecio spp. such as common ragwort (Senecio jacobaea), common groundsel (S. vulgaris), eastern groundsel (S. vernalis) or narrow-leafed ragwort (S. inaequidens) increased on fields used for forage production in Germany and other countries.…”
Section: Introductionmentioning
confidence: 99%